2010
DOI: 10.1128/cvi.00476-09
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Simple, Quantitative, and Highly Sensitive Antibody Detection for Lyme Disease

Abstract: There is currently a need for improved serological tests for the diagnosis and monitoring of Lyme disease, an infection caused by Borrelia burgdorferi. In the present study, we evaluated luciferase immunoprecipitation systems (LIPSs) for use for profiling of the antibody responses to a panel of B. burgdorferi proteins for the diagnosis of Lyme disease. Initially, serum samples from a cohort of patients and controls (n ‫؍‬ 46) were used for training and were profiled by the use of 15 different B. burgdorferi an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
1
32
1
2
Order By: Relevance
“…Given the complex nature of the host immune response to B. burgdorferi infection, the use of multiple serologic assays has been proposed to enhance either test sensitivity or specificity (2,6,12,17,34,35). Tests derived from continuous data generate binary (positive or negative) results when a cutoff value is chosen to achieve a desired specificity (e.g., 99%).…”
mentioning
confidence: 99%
“…Given the complex nature of the host immune response to B. burgdorferi infection, the use of multiple serologic assays has been proposed to enhance either test sensitivity or specificity (2,6,12,17,34,35). Tests derived from continuous data generate binary (positive or negative) results when a cutoff value is chosen to achieve a desired specificity (e.g., 99%).…”
mentioning
confidence: 99%
“…If true, this finding would impact the determination of the background threshold setting for the assay, making it necessary to assign a distinct background threshold for each antigen-isotype combination. To test this hypothesis, we compiled a list from the literature of B. burgdorferi proteins that are known or hypothesized to be seroreactive in humans (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). From this list, a subset of 8 B. burgdorferi antigens was selected for further analysis in our assay due to their ability to be produced in large quantities as recombinant in-frame N-terminal glutathione S-transferase (GST) fusion proteins in E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that each antigen-isotype combination performed uniquely using the current iPCR protocol. These data provided the necessary parameters, including the mean background C q value and the standard deviation of that mean for determining an (24,37,38). The demonstration of iPCR equivalency to 2-tier testing using a panel of antigens led us to surmise that a more simplified version of the protocol using a single hybrid antigen was likely to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Lyme disease) involving DNAsynthesis [42]. Rather complex DNA-synthesis and genomeassembly techniques have been used to generate entire viral genomes and to address the etiology and pathogenicity mechanisms of corresponding viruses, including the viruses that caused the 1918 influenza pandemic or that are responsible for SARS [43,44].…”
Section: (Iii) Synthesis Of Pathogens or Components Thereof For Diagnmentioning
confidence: 99%